“Who is steering the ship and which constellation guides the way? Exploring transparency in the European Central Bank during the time of crisis” - Brunila, Johannes (fi=Turun yliopisto|en=University of Turku|, 2015)
This paper explores transparency in the decision-making of the European Central Bank (ECB). According to ECB´s definition, transparency means that the central bank provides the general public with all relevant information on its strategy, assessments and policy decisions as well as its procedures in an open, clear and timely manner. In this paper, however, the interpretation of transparency is somewhat broader: Information is freely available and directly accessible to those who will be affected by the decisions. Moreover, the individuals shall be able to master this material. ECB´s negative attitude towards publication of documents has demonstrated central bank´s reluctance to strive towards more extensive transparency. By virtue of the definition adopted by the ECB the bank itself is responsible for determining what is considered as relevant information. On the grounds of EU treaties, this paper assesses ECB`s accountability concentrating especially on transparency by employing principal-agent theory and constitutional approach. Traditionally, the definite mandate and the tenet of central bank independence have been used to justify the limited accountability. The de facto competence of the ECB has, however, considerably expanded as the central bank has decisively resorted to non-standard measures in order to combat the economic turbulences facing Europe. It is alleged that non-standard monetary policy constitutes a grey zone occasionally resembling economic policy or fiscal policy. Notwithstanding, the European Court of Justice has repeatedly approved these measures. This dynamic interpretation of the treaties seems to allow temporarily exceptions from the central bank´s primary objective during extraordinary times. Regardless, the paper suggests that the accountability nexus defined in the treaties is not sufficient in order to guarantee the accountability of the ECB after the adoption of the new, more active role. Enhanced transparency would help the ECB to maintain its credibility. Investing in the quality of monetary dialogue between the Parliament and the ECB appears to constitute the most adequate and practicable method to accomplish this intention. As a result of upgraded transparency the legitimacy of the central bank would not solely rest on its policy outputs.